KEPENTINGAN INGGRIS MENDIRIKAN PANGKALAN MILITER (NAVAL BASE) DI MINA BAHRAIN PADA TAHUN 2014 - Rizki Mardatilla; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is intended to analyze England interest to build Naval Base in Mina, Bahrain on 2014. Rising of the conflict escalation in gulf region, on Descember 6, 2014,Phillip Hammond and Hamad bin Isa al-Khalifa Bahrain King accepted to built England military base in Mina Bahrain in 10th Manama Forum. This paper implement qualitativ research with library method research, which data that based on books, journals, artikels, publications and internet. Writer uses security theory fom Bary Buzan with applicate Balance of Power concept, in implementation, England choice hard balancing like T.V. Paul statement. In localize England military base in Mina Bahrain, England send battleship to defused mine in Mina, Bahrain to maintain the stability of middle-east security is influenced by balancing action that has done by England about the threath in MiddleEast, that aimed to Iran nuclear and closing issue about Hormuz Narrow by Iran. This England action is influenced by its national interest in MiddleEast. Aiming this interest, England implement policies like support and defended the Hamad Bin Isa Al Khalifa goverment regime which is pro-western. England goal in bulid the military base in Mina, Bahrain is to pursue and maintain its national interest like economic interest and security interest.Keywords: National Interst, Middle East, Military Base, Security, Stability Of Middle-East, Threat.